Nugget Berbahan Dasar Tepung Kacang Koro Canavalia Ensiformis L. dan Rebung sebagai Upaya Pencegahan Wasting pada Anak Usia 5−12 Tahun: Nuggets from Canavalia Ensiformis L. Koro Beans Flour and Bamboo Shoots as a Prevention for Wasting in Children 5−12 Years - Palimbong, Sarlina; Renyoet, Brigitte Sarah; Yubilenta, Skolastika Weny (Universitas Airlangga, 2024)
Background: Wasting in children can hinder their growth and development, cognitive ability and productivity. Objectives: To create innovative nugget products from Canavalia Ensiformis L. flour and bamboo shoots for wasting prevention for children aged 5–12 years, to determine the acceptability of Canavalia Ensiformis L. flour and bamboo shoots nugget, to measure the nutritional value the product. Methods: The ratios of the ingredients, i.e., Canavalia Ensiformis L. flour and bamboo shoots, are 100:25, 75:50, and 50:75. The proximate test parameters include water, ash, protein, fat, and carbohydrates. Each test was repeated 3 times. The acquired proximate data was processed using one-way ANOVA test; the results indicate significant differences; Duncan test will be conducted. The hedonic test assessing the color, aroma, taste, texture and the overall parameters of the product was carried out on untrained panelist. The obtained hedonic data was processed using the Kruskal-Wallis test. Results: The ratio of the ingredients significantly affects the water, ash, protein, fat, and carbohydrate content of the nuggets. The higher proportion of the Canavalia Ensiformis L. flour, the lower water, ash, and fat content of the nuggets, but the higher their protein and carbohydrate content. However, ratio of the ingredients does significantly influence the acceptability of the nuggets. Conclusions: Formula A, which has the ratio of 100:25, is recommended due to its excellent nutritional values of 27.98% water, 1.98% ash, 18.85% protein, 20.4% fat, and 30.79% carbohydrates. It provides a good sensory acceptance and can be used to prevent wasting in children.